CellFM: a large-scale foundation model pre-trained on transcriptomics of 100 million human cells - Yuansong Zeng; Jiancong Xie; Ningyuan Shangguan; Zhuoyi Wei; Wenbing Li; Yun Su; Shuangyu Yang; Chengyang Zhang; Jinbo Zhang; Nan Fang; Hongyu Zhang; Yutong Lu; et al. (Nature Communications)
Abstract Single-cell sequencing provides transcriptomic profiling at single-cell resolution, uncovering cellular heterogeneity with unprecedented precision. Yet, current single cell data analysis suffers from the inherent data noises, batch effects, and sparsity, highlighting the requirement of a unified model to represent cellular states. To circumvent this problem, many recent efforts focus on training single-cell foundation models based on large datasets. However, current human foundation models are still limited by the sizes of training data and model parameters. Here, we have collected a diverse dataset of 100 million human cells, on which we train a single-cell foundation model (CellFM) containing 800 million parameters. To balance efficiency and performance, the model is trained through a modified RetNet framework on the MindSpore. Extensive experiments have shown that CellFM outperforms existing models in cell annotation, perturbation prediction, gene function prediction, and gene-gene relationship capturing.